Peran Motivasi Dalam Memediasi Pengaruh Pengalaman Kerja dan Kompetensi terhadap Pengembangan Karir Pegawai di PT PLN (Persero) Divisi Sistem dan Teknologi Informasi Operasional Sumatera - Meilly Sumarni; Zulaspan Tupti (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
The purpose of this study was to determine and analyze the role of motivation in mediating the effect of work experience and competence on employee career development at PT PLN (Persero) Operational Information Technology and Systems Division of Sumatra. The research method used is associative research method. Methods of data collection is done by distributing questionnaires and documentation studies. The study was conducted using saturated samples taken from the total population of 80 people. Data processing using Lisrel software version 8.8 with descriptive analysis, classical assumption test, multiple linear regression analysis, hypothesis testing, and coefficient of determination (R2). The results showed that (1) Partially, the work experience variable had a positive and insignificant effect on employee motivation; (2) Partially, the competence variable has a positive and significant effect on employee motivation; (3) Partially the work experience variable has a positive and insignificant effect on employee career development (4) Partially the competence variable has a positive and significant effect on employee career development (5) Partially the motivation variable has a negative and insignificant effect on employee career development (6 ) Motivation variable has no significant effect in mediating the effect of work experience on employee career development (7) motivation variable has no significant effect on mediating the influence of competence variable on employee career development.